Association Between Vaginal Gardnerella and Tubal Pregnancy in Women With Symptomatic Early Pregnancies in China: A Nested Case-Control Study - Zhang, Yingxuan; Chen, Si; Chen, Xiaofeng; Zhang, Huimin; Huang, Xuge; Xue, Xiaomeng; Guo, Yinan; Ruan, Xiaofeng; Liu, Xiaorong; Deng, Gaopi; Luo, Songping; Gao, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
Early diagnosis and intervention for ectopic pregnancy (EP) remains an urgent problem still needs to be solved. The interaction between vaginal microbiota and female reproductive health has attracted increasingly attention. While few studies involved the association between vaginal microbiota and pregnancy location. This nested case-control study aims to characterize the vaginal microbiota in tubal pregnancy (TP) among symptomatic women in early pregnancy. Women with symptomatic early pregnancy of unknown pregnancy location were included in this study. 16S rDNA gene sequencing has been performed to assess the vaginal microbial diversity and structure. Machine Learning and multivariate logistic regression have also been used to evaluate the association between Gardnerella and TP. The results indicated vaginal microbial community in TP showed higher diversity (Shannon, P<0.05), and different composition were shown between TP and intrauterine pregnancy (IUP) (Weighted Unifrac, R=0.08, P=0.01). Genus Gardnerella was significantly enriched in TP. By xgboost analysis, Gardnerella can classify TP more reliably (AUC=0.621). Moreover, after adjusting potential confounders, results indicated a robust association between Gardnerella and TP (as continuous variable, adjusted OR: 12.0, 95% CI: 2.1-67.4, P<0.01; as categorical variable (≥0.85%), adjusted OR: 4.2, 95% CI: 2.0-8.8, P＜0.01). In conclusion, among women with symptomatic early pregnancy, a higher abundance of Gardnerella vaginal microbial abundance was associated with TP.